Pengenalan Computational Thinking Sebagai Metode Problem Solving Kepada Guru SD Di Kabupaten Luwu Utara - Dyah Vitalocca; Nuridayanti; Nurul Mukhlisah Abdal (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
The development of problem-solving skills is crucial in facing global competition. Therefore, early training is necessary. With the advancement of technology and computer usage, a new approach to developing problem-solving skills has emerged, known as Computational Thinking (CT). CT is derived from the fundamental principles of computer science, where problems are understood in an abstract manner and solutions are formulated through illustration. Since 2016, Indonesia has actively participated in the Bebras Community and promoted Computational Thinking by organizing the Bebras Challenge for students across the country. The Faculty of Engineering at UNM has become one of the Bebras Bureaus involved in organizing the Bebras Challenge in South Sulawesi. The Bebras outreach to teachers aims to introduce this Computational Thinking skill so that every teacher can convey and train their students in developing problem-solving skills. The outreach was attended by representative teachers from 100 elementary schools in Kabupaten Luwu Utara